Ataques de negação de serviço em dispositivos Lora - Lopes, Isadora Rezende (2021)
The development of technologies using the Internet of Things concept evolves daily. These numerous technologies, such as LoRa (Long Range) transceivers, are applied in several fields, including the monitoring of natural disasters or disasters caused by human failure. Security vulnerabilities arise along with the development of new technologies or updating of existing devices. Attacks that seek to impact device availability such as Denial of Service attacks can be an effective way of exploiting vulnerabilities in LoRa devices and preventing disaster monitoring from happening. Thus, the present work evaluates the impact of DoS attacks on LoRa devices used in the context of disaster monitoring. For this, experiments were carried out, using the LoRaSim simulator, in order to degrade the performance of the LoRaWAN network proposed for flood monitoring. After carrying out the experiments, it was concluded that there is a high impact on the performance of the network when certain parameters are raised or lowered.